Cool Crosslinking: Riboflavin at 4°C for Pain Management After Crosslinking for Keratoconus Patients, A Randomized Clinical Trial. Issue 1 (January 2021) - Toro-Giraldo, Laura; Morales Flores, Norma; Santana-Cruz, Omar; Ramirez-Miranda, Arturo; Navas, Alejandro; Olivo-Payne, Andrew; Lichtinger, Alejandro; Jimenez-Corona, Aida; Graue-Hernández, Enrique O.
Abstract : Purpose: To explore corneal cooling as a method of pain management in corneal-accelerated collagen cross-linking. Methods: This was a prospective and interventional randomized clinical trial registered in the National Institutes of Health Clinical Trials through the identifier NCT030760770. The research was conducted at the Institute of Ophthalmology "Conde de Valenciana." A total of 98 patients were randomly assigned to one of the following 2 groups: cold riboflavin (4°C) group or control group (riboflavin at room temperature). The inclusion criteria were patients of any sex, older than 18 years of age with keratoconus diagnosis who needed management with cross-linking in both eyes because of the evidence of progression. The exclusion criteria were patients who had cross-linking without epithelial debridement, unilateral cross-linking, or any other ocular pathologies besides keratoconus and any cognitive incapacity that would make the understanding of the pain test difficult. The main outcome measures were pain, tearing, photophobia, foreign body sensation, and irritation. Results: At 2 hours post-op, pain in the case and control groups was 3.80 ± 3.00 and 8.08 ± 2.21 ( P < 0.05), tearing was 1.56 ± 1.96 and 8.29 ± 2.42 ( P < 0.05), photophobia was 5.44 ± 3.57 and 7.83 ± 2.64 ( P < 0.05), foreign body sensation was 2.20 ± 2.78 and 6.54 ± 2.73 ( P < 0.05), and irritation was 3.48 ± 2.98 and 6.79 ± 3.00 ( P < 0.05), respectively. A statistical significant difference was maintained in pain values on day 1 (2.79 ± 3.09 and 4.91 ± 3.27 [ P < 0.05]), 2 (2.54 ± 2.41 and 4.00 ± 2.43 [ P < 0.05]), and 4 (0.45 ± 0.76 and 1.22 ± 1.67 [ P < 0.05]). Conclusions: This study demonstrated that pain and associated symptoms decreased significantly in the riboflavin 4°C group.